To simplify 12^87 ÷ 12^25, you subtract the exponents because the base is the same.
12^87 ÷ 12^25 = 12^(87-25) = 12^62
simplify 12^87 ÷ 12^25
9 answers
what is the missing number in the simplified exponential expression 7^7 ÷ 7^5 = 7^12?
In the simplified exponential expression 7^7 ÷ 7^5 = 7^12, the missing number is the exponent on the right side. The exponent on the right side is 12.
what is the value of 6.9 - 2^0
The value of 6.9 - 2^0 is 6.9 - 1, because any number raised to the power of 0 is 1.
Therefore, 6.9 - 2^0 = 6.9 - 1 = 5.9.
Therefore, 6.9 - 2^0 = 6.9 - 1 = 5.9.
solve the expression 15 · 8^0/5 + 4 (7^0-6)
To solve the expression 15 · 8^0/5 + 4 (7^0-6), we need to follow the order of operations (PEMDAS/BODMAS).
First, we solve within the parentheses:
7^0 = 1
So, the expression becomes:
15 · 8^0/5 + 4(1 - 6)
Next, we calculate the exponent:
8^0 = 1
The expression now looks like:
15 · 1/5 + 4(1 - 6)
Next, we solve within the parentheses:
1 - 6 = -5
The expression simplifies to:
15 · 1/5 + 4(-5)
Now, we simplify the multiplications division from left to right:
15 · 1/5 = 3
Substituting the value, the expression becomes:
3 + 4(-5)
Finally, we solve the multiplication:
4(-5) = -20
The expression simplifies to:
3 - 20 = -17
Therefore, the solution to the expression 15 · 8^0/5 + 4 (7^0-6) is -17.
First, we solve within the parentheses:
7^0 = 1
So, the expression becomes:
15 · 8^0/5 + 4(1 - 6)
Next, we calculate the exponent:
8^0 = 1
The expression now looks like:
15 · 1/5 + 4(1 - 6)
Next, we solve within the parentheses:
1 - 6 = -5
The expression simplifies to:
15 · 1/5 + 4(-5)
Now, we simplify the multiplications division from left to right:
15 · 1/5 = 3
Substituting the value, the expression becomes:
3 + 4(-5)
Finally, we solve the multiplication:
4(-5) = -20
The expression simplifies to:
3 - 20 = -17
Therefore, the solution to the expression 15 · 8^0/5 + 4 (7^0-6) is -17.
15·8^0/5 + 4 (7^0 - 6)
To solve the expression 15·8^0/5 + 4 (7^0 - 6), we first need to evaluate the exponents inside the parentheses.
7^0 = 1 (Any number raised to the power of 0 is equal to 1.)
Now, we can substitute the values into the expression:
15·8^0/5 + 4(1 - 6)
Next, we simplify the exponential expression:
8^0 = 1
Now the expression becomes:
15·1/5 + 4(1 - 6)
Next, we simplify within the parentheses:
1 - 6 = -5
The expression now becomes:
15·1/5 + 4(-5)
Next, we solve the multiplications and divisions from left to right:
15·1/5 = 3 (multiplying 15 by 1 gives us 15, then dividing by 5 gives us 3)
Now the expression becomes:
3 + 4(-5)
Next, we solve the multiplication:
4(-5) = -20 (multiplying 4 by -5 gives us -20)
The expression is now:
3 - 20
Finally, we perform the subtraction:
3 - 20 = -17
So the solution to the expression 15·8^0/5 + 4(7^0 - 6) is -17.
7^0 = 1 (Any number raised to the power of 0 is equal to 1.)
Now, we can substitute the values into the expression:
15·8^0/5 + 4(1 - 6)
Next, we simplify the exponential expression:
8^0 = 1
Now the expression becomes:
15·1/5 + 4(1 - 6)
Next, we simplify within the parentheses:
1 - 6 = -5
The expression now becomes:
15·1/5 + 4(-5)
Next, we solve the multiplications and divisions from left to right:
15·1/5 = 3 (multiplying 15 by 1 gives us 15, then dividing by 5 gives us 3)
Now the expression becomes:
3 + 4(-5)
Next, we solve the multiplication:
4(-5) = -20 (multiplying 4 by -5 gives us -20)
The expression is now:
3 - 20
Finally, we perform the subtraction:
3 - 20 = -17
So the solution to the expression 15·8^0/5 + 4(7^0 - 6) is -17.